2020
DOI: 10.1111/nph.17025
|View full text |Cite
|
Sign up to set email alerts
|

An increase in xylem embolism resistance of grapevine leaves during the growing season is coordinated with stomatal regulation, turgor loss point and intervessel pit membranes

Abstract: Although xylem embolism resistance is traditionally considered as static, we hypothesized that in grapevine (Vitis vinifera) leaf xylem becomes more embolism-resistant over the growing season. We evaluated xylem architecture, turgor loss point (Ψ TLP) and water potentials leading to 25% of maximal stomatal conductance (g s25) or 50% embolism in the leaf xylem (P 50) in three irrigation treatments and at three time points during the growing season, while separating the effects of leaf age and time of season. Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 71 publications
11
68
0
Order By: Relevance
“…It is possible that variation in T PM within a vessel or within the vessel network provides additional chances of leakiness, and small differences in T PM across organs (Kotowska et al ., 2020) could influence embolism resistance. Capturing this variation, however, is difficult because measuring T PM may not be straightforward, for instance due to TEM preparation artefacts, aggregation of cellulose fibrils into larger aggregates, and seasonal shrinkage of pit membranes (Schmid & Machado, 1968; Sorek et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that variation in T PM within a vessel or within the vessel network provides additional chances of leakiness, and small differences in T PM across organs (Kotowska et al ., 2020) could influence embolism resistance. Capturing this variation, however, is difficult because measuring T PM may not be straightforward, for instance due to TEM preparation artefacts, aggregation of cellulose fibrils into larger aggregates, and seasonal shrinkage of pit membranes (Schmid & Machado, 1968; Sorek et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…embolism) (Choat et al ., 2008; Kaack et al ., 2019). Since water transport efficiency is tightly related to transpiration and photosynthesis, drought‐induced embolism formation can have major implications for plant performance, especially under drought (Li et al ., 2016a,b; Sorek et al ., 2021). Yet many details about the mechanistic relationship between embolism formation and the anatomical determinants of pits remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonality is known to affect the hydraulic performance and embolism resistance in woody species (Kolb & Sperry, 1999; Jacobsen et al ., 2014) and, in this study, seasonality may also have affected the degree to which the laboratory‐generated curves agree with the field data. Recent work has shown that seasonal changes in xylem lumen to cell wall ratios, the progressive addition of xylem tissue and ion‐mediated shifts in conductivity have led to some combination of increased cavitation resistance or higher transport efficiency toward the end of the growing season (Jupa et al ., 2019; Sorek et al ., 2020). Similar phenomena may affect fern hydraulics.…”
Section: Discussionmentioning
confidence: 99%
“…It has been ascertained that future global warming scenarios will increase the drought risk in most cultivated regions in the next several decades [1][2][3]. Drought can seriously affect crop yield and quality, and, in exceptional cases, crop survival [4][5][6]. Where applicable, irrigation practices are largely adopted to compensate seasonal water deficit, even though such practices may also generate negative environmental aftermaths [7].…”
Section: Introductionmentioning
confidence: 99%